How to talk with anyone about anything : the practice of safe conversations - Hendrix, Harville; Hunt, Helen, 1949- (Thomas Nelson, 2024)
Relationships everywhere are in crisis due to our inability to have problem-solving, connected conversations. But New York Times bestselling authors Dr. Harville Hendrix and Dr. Helen LaKelly Hunt believe the components of safe conversations are teachable to everyone.